Constrictive epicarditis following Coxsackie virus infection. - Cooper, D K (1976)
A case is presented of the rare condition of constrictive epicarditis, which was treated successfully by removal of the epicardium. This appears to be the first account of constrictive epicarditis following proven Coxsackie viral infection.